Juvenile “idiopathic” arthritis (JIA) as a manifestation of food allergy. Case Study - Muñoz-Urribarri, Ana Beatriz (2020)
Studies linking type of diet and juvenile idiopathic arthritis (JIA) have variable results and are inconsistent. This case shows an evolution which fulfilled the criteria of JIA, but was diagnosed as food allergy. Case: A seven-year old boy had fever, arthralgia, general malaise, headaches, abdominal pain and rashes. These symptoms were diagnosed as fever of unknown origin (FUO) and probable JIA. There was a stabbing pain in the right iliac fossa. An upper and lower endoscopy were performed and nodular ileocolitis was detected. A hypoallergenic diet was prescribed, in addition to mesalazine and oral corticosteroids. The patient was asymptomatic for 2.5 months and then relapsed with all symptoms after consuming dairy. This JIA case shows the diagnostic phases of food allergy: improvement and recurrence of symptoms with the reintroduction of the allergen (oral challenge=gold standard of food allergy). There is evidence that supports the existence of a gut-joint axis, where the luminal content triggers a series of immunologically mediated reactions that can cause systemic diseases such as J other connective tissue diseases. This case report adds reasonable evidence in support of food allergy as a cause of JIA.